Quantitative analyses of maxillary sinus using computed tomography Análise quantitativa dos seios maxilares por meio da tomografia computadorizada - Andréia Perella; Sara dos Santos Rocha; Marcelo de Gusmão Paraiso Cavalcanti (University of São Paulo, 2003)
The aim of this study was to evaluate the precision and accuracy of linear measurements of maxillary sinus made in tomographic films, by comparing with 3D reconstructed images. Linear measurements of both maxillary sinus in computed tomography CT of 17 patients, with or without lesion by two calibrated examiners independently, on two occasions, with a single manual caliper. A third examiner has done the same measurements electronically in 3D-CT reconstruction. The statistical analysis was performed using ANOVA (analyses of variance). Intra-observer percentage error was little in both cases, with and without lesion; it ranged from 1.14% to 1.82%. The inter-observer error was a little higher reaching a 2.08% value. The accuracy presented a higher value. The perceptual accuracy error was higher in samples, which had lesion compared to that which had not. CT had provided adequate precision and accuracy for maxillary sinus analyses. The precision in cases with lesion was considered inferior when compared to that without lesion, but it can't affect the method efficacy. O objetivo deste trabalho foi avaliar a precisão e acurácia de medidas lineares da região de seio maxilar realizadas em filmes tomográficos, por meio de comparação com a reconstrução da imagem em 3D. Medidas lineares de ambos os seios maxilares foram realizadas em tomografias computadorizadas (2D-TC) de 17 pacientes, normais e com lesão, por dois examinadores, calibrados, separadamente, duas vezes cada um, utilizando um compasso. Um terceiro observador realizou as mesmas medidas eletronicamente na reconstrução 3D-TC. ANOVA (análise de variância) foi utilizado para análise estatística. A porcentagem de erro intra-examinadores foi pequena em ambos os casos, com ou sem lesão, variando de 1,14% a 1,82%. O erro inter-examinadores foi maior alcançando o valor de 2,08% .O erro percentual de acurácia nas amostras com lesão foram maiores comparando-as às que não tinham lesão. A tomografia computadorizada em 2D-TC (Em filmes e estação de trabalho independente) proporcionou precisão e acurácia adequadas para análise dos seios maxilares. "O erro foi maior no caso de seios maxilares com lesão,comparando aos lados sem lesão, tanto inter quanto intra-examinadores, sem alterar, porém, a eficácia do método."